2011
DOI: 10.1007/s10534-011-9439-0
|View full text |Cite
|
Sign up to set email alerts
|

Bovine milk lactoferrin induces synthesis of the angiogenic factors VEGF and FGF2 in osteoblasts via the p44/p42 MAP kinase pathway

Abstract: Lactoferrin (LF) belongs to the transferrin family and is present in several physiological fluids, including milk and colostrum. LF has recently been identified as an anabolic factor for bone. Here we investigated whether bovine LF (bLF) induces synthesis of angiogenic factors by osteoblasts. If so, we examined the underlying mechanism. We found that bLF purified from milk increased the mRNA expression of vascular endothelial growth factor (VEGF) and fibroblast growth factor-2 (FGF2) in murine osteoblast-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…12 Recent studies indicate the ability of bLF to promote fibroblast growth factor-2 (FGF-2) and vascular endothelial growth factor (VEGF) synthesis by osteoblasts via the p44/p42 MAP kinase pathway. 13,14 Additionally, bLF has been shown to inhibit osteoclastogenesis in primary culture of murine bone cells at a concentration as low as 10 mg/mL. 9 Collectively, these studies substantiate LF as a positive regulator of the skeleton.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…12 Recent studies indicate the ability of bLF to promote fibroblast growth factor-2 (FGF-2) and vascular endothelial growth factor (VEGF) synthesis by osteoblasts via the p44/p42 MAP kinase pathway. 13,14 Additionally, bLF has been shown to inhibit osteoclastogenesis in primary culture of murine bone cells at a concentration as low as 10 mg/mL. 9 Collectively, these studies substantiate LF as a positive regulator of the skeleton.…”
Section: Introductionmentioning
confidence: 88%
“…In addition to being a bone anabolic factor, LF is known to induce the synthesis of angiogenic factors and pleiotropic cytokines by osteoblasts. 14,15,33 Immunocytochemical studies were performed to confirm the production of IL-6 and VEGF by MC3T3-E1 cells in the presence of apo-and holo-rhLf to evaluate whether the expression of the cytokines is dependent on iron saturation. Figure 3B and C show the immunofluorescence images of MC3T3-E1 cells exposed to 100mg/ mL of apo-and holo-rhLF indicating positive stains for both IL-6 and VEGF.…”
Section: Effect Of Lf Iron Concentration On Mc3t3-e1 Cell Signalingmentioning
confidence: 99%
“…it exerts the strongest effect by intensification of osteoblast differentiation in the early stage of development. In turn, the impact is not as strong in the consecutive stages (25,27,34). Cornish et al (8) and Yoshimaki et al (34) have demonstrated that after application of lactoferrin vBMD is higher than in the ovariectomized control group, which is related to the anabolic effect of LF on osteoblasts and its inhibitory activity towards osteoclasts.…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, at adequate availability of LF over a sufficiently long time, development of osteopenic conditions is impaired and bone reconstruction processes are intensified. Moreover, lactoferrin stimulates phosphorylation of p44/p42 MAP kinase in osteoblasts (25,26,29). In turn, the compounds contained in colostrum reduce or abolish the decline in the Ca level, thereby protecting against the development of osteoporosis.…”
Section: Resultsmentioning
confidence: 99%
“…Our group, along with others, have demonstrated the ability of LF to upregulate the synthesis of growth factors such as VEGF and FGF in MC3T3-E1 preosteoblast cells. 8,26,27 Another potential anabolic molecule that has been shown to play a key role in cell survival, proliferation, and differentiation is IGF. Studies have shown the increased bone turnover via increased osteoblast number and function can be directly and/or indirectly caused by local IGF-1 and IGF-2 production.…”
Section: Cellular Interactions With Blf and Blf Gelmentioning
confidence: 99%